The Inhibitory Effect of Conocarpus Lancifolius Leaf Extract on Protease Produced by Clinical Pseudomonas Aeruginosa Isolate - K. A., Asawer; Shawkat, M. S. (Iraqi Journal of Science, 2023)
The study was aimed at inhibiting the protease produced by Pseudomonas aeruginosa using an 80% alcoholic extract of Conocarpus lancifolius leaves. A total of 146 isolates of P. aeruginosa that were isolated and identified by microscopic and biochemical tests were 51 isolates submitted to primary and secondary screening techniques in order to choose the qualified P. aeruginosa isolate for protease synthesis. Among these isolates, forty-seven isolates showed hydrolysis zones on skim milk media (primary screening); six isolates were chosen for secondary screening. The result revealed that P. aeruginosa P51 had the highest ability to produce the enzyme, with a specific activity of 15.9 U/mg protein. In addition, the study included extracting the leaves of C. lancifolius using 80% ethanolic alcohol and conducting the GC-MC assay and the HPLC assay of the plant extract. The results revealed a significantly decreased specific activity of protease from 15.9 to 1.2 U/mg after treatment with 0.8 µg/ml of alcoholic extract of C. lancifolius leaves.